2012
DOI: 10.1007/s12098-012-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

A Case Control Study on Specific Learning Disorders in School Going Children in Bikaner City

Abstract: The current study, therefore, is an attempt to identify children with learning disorders and explore the prevalence of the problem and etiological factors e.g., family environment, social factors and developmental issues of child and associated co-morbidities. More studies with larger sample size should be undertaken to get accurate picture of these disorders.There is also need for some community based programme to raise the level of awareness and knowledge about these disorders in general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…In present study dyslexic group were approximately equally distributed in the age groups 8, 9, 10 and 11 years and there was no significant difference among different ages and presence of reading disorder which is in consistent with various authors 27,29,30 who all have reported the prevalence of LD in age group of 8-11 years. Our study reveals that 64(9%) children in non-dyslexic group were only child of their parents followed by 289(42%) first born, 255(37%) were last born and 77(12%) were others, where as in the dyslexic group 36 Choudhary et al 27 and Donfrancesco et al 31 However Dhanda & Jagawat 30 have reported a significant difference in birth order of dyslexia and their total sample studied.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In present study dyslexic group were approximately equally distributed in the age groups 8, 9, 10 and 11 years and there was no significant difference among different ages and presence of reading disorder which is in consistent with various authors 27,29,30 who all have reported the prevalence of LD in age group of 8-11 years. Our study reveals that 64(9%) children in non-dyslexic group were only child of their parents followed by 289(42%) first born, 255(37%) were last born and 77(12%) were others, where as in the dyslexic group 36 Choudhary et al 27 and Donfrancesco et al 31 However Dhanda & Jagawat 30 have reported a significant difference in birth order of dyslexia and their total sample studied.…”
Section: Discussionsupporting
confidence: 92%
“…Our study reveals that 64(9%) children in non-dyslexic group were only child of their parents followed by 289(42%) first born, 255(37%) were last born and 77(12%) were others, where as in the dyslexic group 36 Choudhary et al 27 and Donfrancesco et al 31 However Dhanda & Jagawat 30 have reported a significant difference in birth order of dyslexia and their total sample studied. Therefore, these results are in contradiction to the present ones.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…8 In a study from Bikaner, the sex ratio was 11.4% vs 7.4%. 9 In previous studies, median age of presentation was 11.4 years while our study had median age of 14 years, with youngest being 7 year old. 8 Al-mamari et al found Mean age of children with learning disorders in Omani children was 8.5 years.…”
Section: Discussionmentioning
confidence: 50%